PENERAPAN MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DITINJAU DARI PERBEDAAN GENDER DALAM MATERI BARISAN DAN DERET ARITMATIKA PADA SISWA SMA - Nur Fadillah Utami; Muhamad Firdaus; Yudi Darma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is a difference in the auditory intellectually repetition learning model on mathematical problem solving abilities in terms of gender differences in the material of arithmetic sequences and series in high school students. This study is a quantitative study of the Quasy Experimental type. Data were obtained from a mathematical problem solving ability test given to students. The data analysis technique used a two-way ANOVA test and further testing using a multiple comparison test with the Sheffe method. Based on the results of the analysis and discussion of the research data, the results showed that the Auditory Intellectually Repetition learning model has better mathematical problem solving abilities than the direct learning model. Female students have better mathematical problem solving abilities than male students. in the category of the Auditory Intellectually Repetition model and the direct learning model, female students have better mathematical problem solving abilities than male students. In the category of female and male students, the Auditory Intellectually Repetition model has better mathematical problem solving abilities than the direct learning model.